2001
DOI: 10.1002/1529-0131(200111)44:11<2562::aid-art437>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decrease in susceptibility of human articular cartilage to matrix metalloproteinase-mediated degradation: The role of advanced glycation end products

Abstract: Objective Progressive destruction of articular cartilage is a hallmark of osteoarthritis (OA) and rheumatoid arthritis (RA). Age‐related changes in cartilage may influence tissue destruction and thus progression of the disease. Therefore, the effect of age‐related accumulation of advanced glycation end products (AGEs) on cartilage susceptibility to proteolytic degradation by matrix metalloproteinases (MMPs) present in synovial fluid (SF) of OA and RA patients was studied. Methods Cartilage was incubated with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 60 publications
4
74
0
1
Order By: Relevance
“…Therefore, age-related changes in articular cartilage that influence the composition and strength of the cartilage matrix are very likely involved in the development of OA (55). One such change, the agerelated accumulation of AGEs, has previously been shown to increase tissue stiffness, decrease extracellular matrix turnover (synthesis and degradation), and affect many cellular processes (13,14,20,21,28,34,47,56). In the present study, we demonstrated in an in vivo model that this process of NEG is indeed causally involved in the age-related increase in susceptibility to OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, age-related changes in articular cartilage that influence the composition and strength of the cartilage matrix are very likely involved in the development of OA (55). One such change, the agerelated accumulation of AGEs, has previously been shown to increase tissue stiffness, decrease extracellular matrix turnover (synthesis and degradation), and affect many cellular processes (13,14,20,21,28,34,47,56). In the present study, we demonstrated in an in vivo model that this process of NEG is indeed causally involved in the age-related increase in susceptibility to OA.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, 25-50 l of SF was collected from control joints and Ͼ150 l from experimental knees. Metalloproteinase activity in SF (final dilution 1:20 in 50 mM Tris [pH 7.5], 5 mM CaCl 2 , 150 mM NaCl, 1 M ZnCl 2 , 0.01% Brij-35, 0.02% NaN 3 ) was determined with fluorogenic substrate TNO211-F (5 M) in the presence of an EDTA-free general proteinase inhibitor (Complete; Roche, Indianapolis, IN) (47,48). This assay is considered to represent overall metalloproteinase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an increase in advanced glycation end products was shown to result in decreased cartilage degradation by MMPs (24). Thus, it has been suggested that the level of cartilage glycation may influence the progression of degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Broad-spectrum MMP activity was determined in 71 out of 73 CRC patient samples (in two cases insufficient sample was left after zymography to perform the activity assay) using the quenched fluorogenic peptide substrate TNO211-F (Dabcyl-Gaba-Pro-GlnGly-Leu-Cys(Fluorescein)-Ala-Lys-NH 2 ) essentially as described previously (Beekman et al, 1999;DeGroot et al, 2001). The substrate is mainly cleaved by the gelatinases (MMP-2 and -9) and collagenase 3 (MMP-13) and to a lesser extent by collagenase 2 (MMP-8) and membrane-bound metalloproteinase (MT1 -MMP).…”
Section: Fluorometric Mmp Activity Assaymentioning
confidence: 99%